Repurposing of Biologic and Targeted Synthetic Anti-Rheumatic Drugs in COVID-19 and Hyper-Inflammation: A Comprehensive Review of Available and Emerging Evidence at the Peak of the Pandemic - Cavalli, Giulio; Farina, Nicola; Campochiaro, Corrado; De Luca, Giacomo; Della-Torre, Emanuel; Tomelleri, Alessandro; Dagna, Lorenzo (Frontiers in Pharmacology, 2020)
Coronavirus disease 2019 (COVID-19) is a condition caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Severe cases of COVID-19 result in acute respiratory distress syndrome and death. A detrimental, hyper-inflammatory immune response with excess release of cytokines is the main driver of disease development and of tissue damage in these patients. Thus, repurposing of biologic agents and other pharmacological inhibitors of cytokines used for the treatment of various inflammatory conditions emerged as a logical therapeutic strategy to quench inflammation and improve the clinical outcome of COVID-19 patients. Evaluated agents include the interleukin one receptor blocker anakinra, monoclonal antibodies inhibiting IL-6 tocilizumab and sarilumab, monoclonal antibodies inhibiting granulocyte-monocyte colony stimulating factor and tumor necrosis factor, and Janus kinase inhibitors. In this review, we discuss the efficacy and safety of these therapeutic options based on direct personal experience and on published evidence from observational studies and randomized clinical trials.